A Review of the Botany, Traditional Use, Phytochemistry, Analytical Methods, Pharmacological Effects, and Toxicity of Angelicae Pubescentis Radix. (3rd August 2020) - Yang, Liu; Hou, Ajiao; Wang, Song; Zhang, Jiaxu; Man, Wenjing; Guo, Xinyue; Yang, Bingyou; Jiang, Hai; Kuang, Haixue; Wang, Qiuhong
Abstract : Angelicae Pubescentis Radix (AP), as a traditional Chinese medicine (TCM), has been used for thousands of years in China. In this paper, the botany, traditional use, phytochemistry, analytical methods, quality control, pharmacological effects, and toxicity of AP were reviewed. It can provide a reference for the further research and lay a foundation for the rational clinical application of AP. The relevant information on AP was collected from scientific databases (such as Baidu Scholar, CNKI, Google Scholar, PubMed, Science Direct, Web of Science, and SciFinder Scholar), Chinese herbal classics, Chinese Pharmacopoeia, PhD and MSc dissertations, and so on. The components which have been isolated and identified in AP include coumarins, volatile oils, organic acids, terpenes, polysaccharides, flavonoids, sterols, and trace elements. Most of them were analyzed by HPLC and GC. A pharmacological study shows that the AP has extensive pharmacological effects, including anti-inflammatory, antirheumatism, sedative and hypnotic, neuroprotection, antioxidation, antitumor, and allergy, and it is widely used in the treatment of the rheumatoid arthritis, knee osteoarthritis, lumbar disc, ankylosing spondylitis, headaches, stroke hemiplegia, Alzheimer's, and arrhythmia. AP is a valuable natural medicinal plant. So far, significant advances have been made in phytochemistry and pharmacology. Some traditional uses have been demonstrated by modern pharmacology. However, the chemical components and pharmacological effects of AP are complex and varied, and there are different standards for the evaluation of its quality and efficacy. The mechanism of action, the structure-activity relationship among the components, and the potential synergistic and antagonistic effects remain to be studied. At the same time, there are few studies on the specific compounds related to its pharmacodynamics. In order to better develop and utilize AP, we should establish a more reasonable, reliable, and accurate quality control standard and focus on the study of bioactive constituents and the demonstration of their mechanism of action.